Multisite Phosphorylation of Human Liver Cytochrome P450 3A4 Enhances Its gp78- and CHIP-mediated Ubiquitination: A PIVOTAL ROLE OF ITS SER-478 RESIDUE IN THE gp78-CATALYZED REACTION - Wang, YongQiang (The American Society for Biochemistry and Molecular Biology, 2012)
CYP3A4, an integral endoplasmic reticulum (ER)-anchored protein, is the major human liver cytochrome P450 enzyme responsible for the disposition of over 50% of clinically relevant drugs. Alterations of its protein turnover can influence drug metabolism, drug-drug interactions, and the bioavailability of chemotherapeutic drugs. Such CYP3A4 turnover occurs via a classical ER-associated degradation (ERAD) process involving ubiquitination by both UBC7/gp78 and UbcH5a/CHIP E2-E3 complexes for 26 S proteasomal targeting. These E3 ligases act sequentially and cooperatively in CYP3A4 ERAD because RNA interference knockdown of each in cultured hepatocytes results in the stabilization of a functionally active enzyme. We have documented that UBC7/gp78-mediated CYP3A4 ubiquitination requires protein phosphorylation by protein kinase (PK) A and PKC and identified three residues (Ser-478, Thr-264, and Ser-420) whose phosphorylation is required for intracellular CYP3A4 ERAD. We document herein that of these, Ser-478 plays a pivotal role in UBC7/gp78-mediated CYP3A4 ubiquitination, which is accelerated and enhanced on its mutation to the phosphomimetic Asp residue but attenuated on its Ala mutation. Intriguingly, CYP3A5, a polymorphically expressed human liver CYP3A4 isoform (containing Asp-478) is ubiquitinated but not degraded to a greater extent than CYP3A4 in HepG2 cells. This suggests that although Ser-478 phosphorylation is essential for UBC7/gp78-mediated CYP3A4 ubiquitination, it is not sufficient for its ERAD. Additionally, we now report that CYP3A4 protein phosphorylation by PKA and/or PKC at sites other than Ser-478, Thr-264, and Ser-420 also enhances UbcH5a/CHIP-mediated ubiquitination. Through proteomic analyses, we identify (i) 12 additional phosphorylation sites that may be involved in CHIP-CYP3A4 interactions and (ii) 8 previously unidentified CYP3A4 ubiquitination sites within spatially associated clusters of Asp/Glu and phosphorylatable Ser/Thr residues that may serve to engage each E2-E3 complex. Collectively, our findings underscore the interplay between protein phosphorylation and ubiquitination in ERAD and, to our knowledge, provide the very first example of gp78 substrate recognition via protein phosphorylation.